Hydrothermal synthesis of oxygen functionalized S–P codoped g-C3N4 nanorods with outstanding visible light activity under anoxic conditions. Issue 48 (16th November 2015) - Hu, Shaozheng; Ma, Lin; Xie, Ying; Li, Fayun; Fan, Zhiping; Wang, Fei; Wang, Qiong; Wang, Yanjuan; Kang, Xiaoxue; Wu, Guang
Abstract : S–P codoping and oxygen functionalization influence the physical property, structural property, optical property and band gap energy of g-C3 N4, which increases the anoxic RhB photo-degradation constant by ∼13 times. Abstract : Extending the application of photocatalytic oxidation technology to the anoxic removal of organic pollutants that exist under some oxygen-free conditions is attractive but challenging. In this study, oxygen functionalized S–P codoped g-C3 N4 nanorods with outstanding visible light activity under anoxic conditions are synthesized using a hydrothermal post-treatment. S and P codoping inhibits the crystal growth of graphitic carbon nitride, enhances the S BET, decreases the band gap energy, and increases the separation efficiency of photogenerated electrons and holes, which increases the anoxic photocatalytic RhB degradation constant by approximately 6.5 times. Oxygen functionalization not only increases the adsorption ability of graphitic carbon nitride but also captures the photogenerated electrons to produce photogenerated holes for RhB degradation under anoxic conditions, leading to a doubling of the RhB degradation constant. This study provides new insight into the design and fabrication of anoxic photocatalysts.